An audit to analyze the three-week-wait pathway at department of otolaryngology, head and neck surgery, Sligo university hospital - Hussain, Tanvir; Moriarty, Aisling; Tighe, Linda (International Journal of Research in Medical Sciences, 2023)
Background: Otolaryngology, head and neck surgery is an area of medicine concerned with diseases of the ear, nose, throat, head and neck regions. The Three-week wait pathway was introduced in Ireland as a way to improve access to specialist care for patients with symptoms suggestive of malignancy. The pathway allows patients to be seen by a specialist within three weeks of referral from their general practitioner. This study is aimed to study the three-week wait-pathway at the department of otolaryngology head and neck surgery, its functioning and how it can be applied in the department to reduce delays. Methods: The quantitative and qualitative research was conducted during one year from January 2021 to December 2021. Results: The results from the audit showed an average of 22 days on referral and an average of 70 days between the times a patient enters the facility and gets out after medical decision making is done. According to the audit, the three-week wait-pathway at department of otolaryngology Head and Neck surgery Sligo university hospital is effective. There are no significant delays in referrals or appointments, and patients are generally happy with the care they receive. The audit found good communication practices within the department, as measured by patient satisfaction scores. Conclusions: This audit has looked at a variety of aspects of the pathway, including its effectiveness in diagnosing and treating patients, its impact on patient satisfaction, and its cost-effectiveness. The evidence suggests that the three-week wait pathway is an effective way to improve patient care and outcomes. Some quality improvement strategies would be necessary to optimize patient flow and clinical efficiency.